Analisis Strategi Promosi UMKM di Lingkungan Universitas Muhammadiyah Sumatera Utara - Srimasyuli Manullang (Universitas Muhammadiyah Sumatera Utara, 2021)
This research was conducted on micro, small and medium enterprises in the Muhammadiyah University of North Sumatra, the purpose of the research was to find out the promotion strategy of micro, small and medium enterprises in the Muhammadiyah University of North Sumatra. The research carried out is a descriptive qualitative approach with explanations and information that will be associated with theories that will be discussed in qualitative research and provide conclusions from this research. The subjects of this study were UMKM actors around the Muhammadiyah University of North Sumatra campus. The data collection techniques used are literature study, observation, interviews and documentation, the data sources used are primary and secondary data, and data analysis consists of inductive techniques, deductive techniques and drawing conclusions. The results obtained regarding the promotion strategy of micro, small and medium enterprises in the Muhammadiyah University of North Sumatra using the concept of a promotional mix including the application of personal selling strategies (Personal Selling), advertising promotions (Advertising), using promotional media and sales promotions (Sales Promotion) with the application of strategies They are able to increase their income during the COVID-19 pandemic.Keywords: Promotion Strategy, Micro, Small and Medium Enterprises